Perancangan Convention Dan Exhibition Di Kecamatan Pedurungan Semarang Dengan Arsitektur Metafora - Rezza Syafiq Syahrian; Sri Kurniasih; Putri Suryandari (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2020)
Increasing business development in Central Java, especially the Pedurungan District of Semarang City, as a city of trade and services, must be supported by the construction of supporting facilities for these activities. By seeing the potential of the city and the limited exhibition facilities available in the city of Semarang, we need a facility that is able to accommodate various events with all the supporting facilities that are very adequate. As the City of MICE. It is hoped that the City of Semarang will be on par with other metropolitan cities, in order to realize Semarang Equivalents, commitment and support is needed. All events related to MICE must be integrated and can be mapped and published on a large scale in order to be visited by local, regional, national and international communities, and dare to attract all national and international events to be held in the city of Semarang.